X-Ray of One-Sided "White Lung" after Central Venous Catheterization. (19th January 2014) - Casanova, Michel; Ummenhofer, Wolfgang
Abstract : Complications during insertion of a subclavian central venous line are rare but potentially serious. This case report describes the radiological abnormality of a one-sided pleural effusion during a routine control directly after a difficult central venous catheterization. We illustrate the findings, the initial emergency management, and our procedure to rule out an iatrogenic hemothorax. Possible differential diagnoses and strategies for management of a suspected complication are discussed.